Ações afirmativas no ensino superior, políticas públicas e direitos humanos : uma análise da implantação das cotas raciais na Universidade Estadual da Paraíba - Silva, João Maria Felisberto da (2024)
Affirmative actions are compensatory and reparatory public policies that seek to promote social inclusion and material equality, for certain social segments that have been inferior and weakened throughout social history. Affirmative actions aim to reveal structural inequalities and their impacts on education and the world of work, creating opportunities to compensate for the processes of social and educational exclusion of the Afro-Brazilian population, as a way of eliminating the processes of social discrimination and racism that affect the social strata most vulnerable in society. The research starts from the existence of racial discrimination, making the Brazilian State responsible for creating public policies to promote racial equality, as a way of overcoming the slavery legacy and the historical omission of the Brazilian State, promoting and implementing the constitutional principle of material equality. The objective of the research is to analyze the implementation of racial quotas in higher education and in a limited way to study access and retention in undergraduate courses at the Center for Science, Technology and Health/CCTS, at the State University of Paraíba, from the year 2021 to the year 2023 This is a qualitative research within the scope of the PPGDH-UFPB in which it aggregates bibliographical and documentary data (administrative, legislative and academic) relating to indicators of access, adaptability and permanence of university students specifically at the Center for Science, Technology and Health, Campus VIII, of the State University of Paraíba, identifying its possibilities of guaranteeing the right to education with the social inclusion of black and brown people in higher education, as a way of combating racial discrimination, strengthening commitments for the affirmation of Human Rights, the realization of rights fundamental principles and constitutional principles of material equality, human dignity and the implementation of the Democratic Rule of Law in the country, proclaimed by the Constitution of the Federative Republic of Brazil. The research brought the results of the implementation of the public policy of racial quotas in public higher education at UEPB, which reduced a historical inequality caused by racial issues, in access and permanence between blacks and whites in the educational system at the UEPB institution. The work concludes that the implementation of the public policy of racial quotas in public higher education at UEPB encourages the recovery of the historical debt that Brazil owes to the black population, effectively complying with constitutional precepts.